Short-term effects of understory removal on understory diversity and biomass of temperate forests in northeast China - Zhang, Yanyan; Yuan, Quan; Deng, Jiaojiao; Zhou, Li; Yu, Dapao; Zhou, Wangming; Wang, Qing-Wei (Frontiers in Forests and Global Change, 2024)
Introduction Understory removal is a traditional practice in forest management to reduce fire risk and promote seedling regeneration. However, its effect on understory diversity, biomass and soil nutrients in temperate forest ecosystems is less known, which limits our assessment of the effectiveness of understory vegetation management. Methods We quantified the composition of the understory species, their diversity, and the biomass of the understory and factors driving changes in these parameters in primary mixed broad-leaved Pinus koraiensis forest (BKF), secondary Betula platyphylla forest (BF), and Larix gmelinii plantation (LF) in northeast China after a 5-year understory removal. Results After understory removal, the number of shrub and herb species in BKF and LF decreased, while the number of shrub species in BF increased significantly and that of herb species decreased; the species with strong light preference, Equisetum hyemale, Impatiens noli-tangere, and Filipendula Palmata, were dominant in the herb layer of the three forest types; Shannon–Wiener diversity, Pielou evenness, and Simpson diversity of the herb layer in LF increased significantly (P < 0.05), while those of the shrub and herb layers in BF and LF showed no significant changes (P > 0.05). The total understory biomass of understory of BKF and LF decreased by 0.94 t·hm−2 and 1.32 t·hm−2, respectively, while that of BF increased by 1.31 t·hm−2; soil NH4+-N and total phosphorus (TP) were the key factors regulating understory vegetation diversity and biomass, respectively. Conclusion These results suggest that understory removal is a beneficial management strategy for increasing shrub biomass and diversity in secondary forests, while it should be avoided in primary forests and plantations to prevent the reduction of understory plant diversity and soil nutrient loss.